First record of Tellimya tenella (Lovén, 1846) in the Italian waters - Strafella, Pierluigi (Array, 2019)
Alive specimens belonging to Tellimya tenella (Lovén, 1846) were recorded for the first time in Adriatic Sea. Up to date, only few pleistocene fossils or empty valves of this species had been reported in Italian waters.